2015
DOI: 10.4028/www.scientific.net/amm.724.192
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Research on Geometric Parameters of Scallop-Shaped Lattice Shells

Abstract: <p>Free-form and bionic spatial shells are popular in the area of spatial structures. Scallop-shaped surface is the product of evolution and a kind of spatial shells that can satisfy the mechanical requirements. Based on the scallop-shaped lattice shells, this paper focused on the optimization of geometric parameters. The principle of minimum strain energy was applied to conclude the influence law of the geometric parameters on mechanical properties. Finally the optimal values of geometric parameters wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…IV E 4. The latter models, dubbed non-minimal entropic, are based on replacing the tachyonic isocurvature field during the ekpyrotic phase, which we focus on in the following, by a non-minimally coupled entropic field as first proposed in [169,170]. These models still encompass non-Gaussianity from the conversion mechanism.…”
Section: E Non-gaussianitiesmentioning
confidence: 99%
See 4 more Smart Citations
“…IV E 4. The latter models, dubbed non-minimal entropic, are based on replacing the tachyonic isocurvature field during the ekpyrotic phase, which we focus on in the following, by a non-minimally coupled entropic field as first proposed in [169,170]. These models still encompass non-Gaussianity from the conversion mechanism.…”
Section: E Non-gaussianitiesmentioning
confidence: 99%
“…This work superseded that of [170] which set up the building blocks to obtain scale-invariant entropy perturbations within the ekpyrotic scenario via non-minimally coupled massless scalar fields. There, it was suggested that the entropy perturbation could be converted into curvature perturbations by means of a curvaton, as done in [169], or modulated (p)reheating [245].…”
Section: F Nonsingular Bounces Via a Galileonmentioning
confidence: 99%
See 3 more Smart Citations